2021
DOI: 10.1097/hjh.0000000000002767
|View full text |Cite
|
Sign up to set email alerts
|

Enterococcus faecalis contributes to hypertension and renal injury in Sprague-Dawley rats by disturbing lipid metabolism

Abstract: Increasing studies have demonstrated that gut microbiota play vital roles in the development of hypertension. However, the underlying mechanism is not fully understood. Methods:The relative abundance of Enterococcus faecalis was determined in the faecal samples of angiotensin II or deoxycorticosterone acetate/salt-induced hypertensive rats. Then, E. faecalis culture was administered orally to rats for 6 weeks. Blood pressure (BP) was measured, renal injury was estimated and a serum metabolomic analysis was per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 47 publications
2
13
0
Order By: Relevance
“…Our result did not demonstrate changes in the urine output or albuminuria in VOO or Bch diets compared to standard diet, indicating no renal damage. The development of hypertension and renal damage associated to HFDs also have a link with changes in gut microbiota [55][56][57]. However, the outcomes of these cardiometabolic and renal diseases could be improved by the use of pro-and prebiotics with the diet [58,59].…”
Section: Discussionmentioning
confidence: 99%
“…Our result did not demonstrate changes in the urine output or albuminuria in VOO or Bch diets compared to standard diet, indicating no renal damage. The development of hypertension and renal damage associated to HFDs also have a link with changes in gut microbiota [55][56][57]. However, the outcomes of these cardiometabolic and renal diseases could be improved by the use of pro-and prebiotics with the diet [58,59].…”
Section: Discussionmentioning
confidence: 99%
“…However, ALD-induced microbial dysbiosis led to the dominance of Escherichia-Shigella and Enterococcus ( Liu et al, 2004 ; Bajaj et al, 2012 ; Tuomisto et al, 2014 ), suggesting a decrease in intestinal amino acid metabolism, which can affect not only the intestinal tract and serum, but also muscle and brain metabolism ( Kirpich et al, 2015 ). Additionally, the dominance of Escherichia - Shigella and Enterococcus have a negative correlation with lipid, nucleotide, and vitamin metabolism, suggesting that they can adversely affect overall intestinal metabolism ( Zhu et al, 2021 ). It has also been reported that intestinal microbial dysbiosis induced by alcohol consumption may lead to changes in microbial primary metabolism, suggesting that it may also affect the intestinal tract as well as surrounding organs, including the liver ( Zhong and Zhou, 2014 ; Bajaj, 2019 ; Fairfield and Schnabl, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, lignans can stimulate the growth of Lactobacillus strains and inhibit the growth of Enterococcus faecalis ( Favela-Hernandez et al, 2012 ; Stojanov et al, 2021 ). Increased Lactobacillus and decreased Enterococcus can help to lower blood pressure ( GĂłmez-Guzmán et al, 2015 ; Wilck et al, 2017 ; Robles-Vera et al, 2020b ; Zhu et al, 2021 ). In addition, in the current study, EU significantly changed the composition of the gut microbiota, which is consistent with a previous study on the anti-hypertensive effects of the combination of Eucommia ulmoides and Tribulus terrestris ( Qi et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%